Rapid preparation of extremely highly permeable covalent organic polymers nanofiltration membranes for alcohol recovery via interfacial polymerization - Yuhao Chen; Xun Zhou; Tengfang Zhang; Baosheng Ge; Q. Jason Niu; Haixiang Sun (Advanced Membranes)
Covalent organic polymers (COPs) membranes have been widely investigated in recent years for the application and preparation of composite nanofiltration (NF) membranes due to the abundant pore structure. However, there are still difficulties in the easy and reliable preparation of scalable and highly permeable COPs membranes. In this work, the polyaminophenylene (PAP) layer was constructed on polysulfone (PSF) ultrafiltration membranes by diazonium-induced anchoring process (DIAP), and then used as a substrate to prepare ultra-thin and highly permeable COPs NF membranes by interfacial polymerization (IP) in only 20 ​s. The presence of PAP layer increases the aqueous phase monomer storage to promote the forward progression and limits the reaction zone of IP, thus resulting in ultrathin and highly crosslinked COPs membranes. In addition, the PAP layer covalently grafted onto the PSF molecular chain also participates in the IP reaction, thus the separation layer is connected to the substrate as a whole for better stability and can operate for long periods of time in an alcohol-based organic solvent environment. The methanol permeance of optimal NF-PAP membrane prepared based on the above strategy can reach 362-398 ​L−1m−2h−1bar−1, which almost achieves an order of magnitude enhancement relative to other reported COPs organic solvent nanofiltration (OSN) membranes. The retention rate of the COPs composite membrane for naphthol green B (Mw ​= ​878) dye was about 98.5 ​%, demonstrating good alcohol recovery ability. In conclusion, this study offers a potential strategy for the development and application of COPs OSN membranes.